Harmonizing hope: navigating the osteoarthritis melody through the CCL2/CCR2 axis for innovative therapeutic avenues - Abbasifard, Mitra; Khorramdelazad, Hossein (Frontiers in Immunology, 2024)
Osteoarthritis (OA) is characterized by a complex interplay of molecular signals orchestrated by the CCL2/CCR2 axis. The pathogenesis of OA has been revealed to be influenced by a multifaceted effect of CCL2/CCR2 signaling on inflammation, cartilage degradation, and joint homeostasis. The CCL2/CCR2 axis promotes immune cell recruitment and tips the balance toward degeneration by influencing chondrocyte behavior. Insights into these intricate pathways will offer novel therapeutic approaches, paving the way for targeted interventions that may redefine OA management in the future. This review article explores the molecular symphony through the lens of the CCL2/CCR2 axis, providing a harmonious blend of current knowledge and future directions on OA treatment. Furthermore, in this study, through a meticulous review of recent research, the key players and molecular mechanisms that amplify the catabolic cascade within the joint microenvironment are identified, and therapeutic approaches to targeting the CCL2/CCR axis are discussed.